2020
DOI: 10.5194/acp-20-3777-2020
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol hygroscopicity and its link to chemical composition in the coastal atmosphere of Mace Head: marine and continental air masses

Abstract: Abstract. Chemical composition and hygroscopicity closure of marine aerosol in high time resolution has not been achieved yet due to the difficulty involved in measuring the refractory sea-salt concentration in near-real time. In this study, attempts were made to achieve closure for marine aerosol based on a humidified tandem differential mobility analyser (HTDMA) and a high-resolution time-of-flight aerosol mass spectrometer (AMS) for wintertime aerosol at Mace Head, Ireland. The aerosol hygroscopicity was ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 53 publications
3
17
0
Order By: Relevance
“…In Clean-H, the smaller particles exhibited higher hygroscopicity, while in Clean-L, it was the larger particles that were more hygroscopic. This pattern is attributed to the presence of Aitken mode near-hydrophobic particle in Clean-L, as highlighted in the previous study (Xu et al, 2020). The AR of less than 100% in Clean-L suggested that treating winter time marine aerosol as pure sea-salt or their mixture with nss-SO4 will likely induce an over-estimation of NCCN at higher SS.…”
Section: Measured Ccn Concentration and Aerosol Size Distributionsupporting
confidence: 67%
See 3 more Smart Citations
“…In Clean-H, the smaller particles exhibited higher hygroscopicity, while in Clean-L, it was the larger particles that were more hygroscopic. This pattern is attributed to the presence of Aitken mode near-hydrophobic particle in Clean-L, as highlighted in the previous study (Xu et al, 2020). The AR of less than 100% in Clean-L suggested that treating winter time marine aerosol as pure sea-salt or their mixture with nss-SO4 will likely induce an over-estimation of NCCN at higher SS.…”
Section: Measured Ccn Concentration and Aerosol Size Distributionsupporting
confidence: 67%
“…S5), while the Aitken mode aerosol consisted of a fraction of near-hydrophobic particles (Fig. S5), which was not discerned by the bulk chemical composition due to negligible mass (Xu et al, 2020). As shown in Fig.…”
Section: Clean Sectormentioning
confidence: 92%
See 2 more Smart Citations
“…Fourth, HMS, CH 3 SO 3 − , and Ca 2+ and Mg 2+ in fine dust are included in the ISORROPIA calculations. We assume the same hygroscopicity of HMS and MSA as sulfate (Xu et al, 2020).…”
Section: Control Simulationmentioning
confidence: 99%